AB0795 Long-term efficacy and safety of rituximab in systemic sclerosis refractory to conventional immunosuppressants. (12th June 2018) - Polito, P.; Zanatta, E.; Favaro, M.; Felicetti, M.; Oliviero, F.; Pigatto, E.; Cozzi, F.; Doria, A.
Abstract : Background: Recent studies 1 2 have shown that B-cells are involved in the pathogenesis of systemic sclerosis (SSc) suggesting that B-cell depletion might have a role in the treatment of the disease 3 . Objectives: To describe the long-term efficacy and safety profile of Rituximab (RTX) in SSc patients who failed previous conventional immunosuppressive drugs. Methods: We retrospectively analysed medical records of all SSc patients treated with Rituximab in our Rheumatology Unit from July 2011 to December 2017. Disease manifestations, particularly skin, pulmonary and articular involvement, were evaluated at baseline (T0), at 8±2 months (T1) and at the last follow-up visit (T2). Results: Thirteen patients, 11 females and 2 males, were treated with 32 RTX cycles (median per patient 2.5, range 1–4). Eleven patients had diffuse and 2 limited cutaneous form; all had positive ANA, 9 anti-TopoI, 2 anti-RNA polIII, and 1 anti-SSA. The mean age at first RTX infusion was 49.3±13.6 years and the mean disease duration was 6.5±3.3 years. The main indications to RTX were: interstitial lung disease (11/13), worsening of skin involvement (6/13) and arthritis (5/13), refractory to at least one previous immunosuppressive drug (median 2, range 1–3). Twelve patients were treated with mycophenolate mofetile, 5 with cyclophosphamide, 4 with methotrexate and 2 with azathioprine. All patients were treated with RTX (1000 mg twice, two weeks apart). Twelve patients received more than one cycle; the interval between cycles was 12.7±5.4 months. The mean follow-up period was 41.4±21.9 months. Five patients had arthritis and we observed complete remission of arthritis in all of them. 8 months after the first RTX administration arthritis relapsed in 4 patients who were successfully retreated. We did not observe a significant decrease in modified Rodnan Skin Score over time (T0: 15.6±6.9, T1: 14.6±7.8, and T2: 13.1±8.3; p=ns). Lung involvement, detected in 11/13 patients, remained radiologically stable in 8 patients and worsened in 3. No significant changes in the pulmonary function tests was observed from T0 to T2. Five patients had a follow-up longer than 33 months after the last RTX cycle: 3 patients had a stable disease, 1 developed severe PAH and 1 lung neoplasia. CD19 cell depletion (<2%) was observed after each RTX cycle, without significant changes in immunoglobulin levels. No infusion reactions were observed. We registered only one severe side effect: hand cellulitis in a patient with digital ulcer, requiring hospitalisation. Conclusions: Our experience suggests that RTX is well tolerated and could be effective in the management of severe and refractory SSc manifestations. References: [1] Dumoitier N, Chaigne B, Régent A, et al. Scleroderma Peripheral B Lymphocytes Secrete Interleukin-6 and Transforming Growth Factor β and Activate Fibroblasts. Arthritis Rheumatol. 2017May;69(5):1078–1089. [2] Daoussis D, Melissaropoulos K, Sakellaropoulos G, et al. A multicenter, open-label, comparative study of B-cell depletion therapy with Rituximab for systemic sclerosis-associated interstitial lung disease. Semin Arthritis Rheum. 2017Apr;46(5):625–631. [3] Jordan S, Distler JH, Maurer B, et al. Effects and safety of rituximab in systemic sclerosis: an analysis from the European Scleroderma Trial and Research (EUSTAR) group. Ann Rheum Dis. 2015Jun;74(6):1188–94. Disclosure of Interest: None declared